Technical reviewing for the Family First Prevention Services Act: Strategies and recommendations. (December 2020) - Garcia, Antonio R.; Pecora, Peter J.; Schnell, Audrey H.; Burnson, Cynthia; Harris, Elizabeth; Finseth, Allison
Highlights: FFPSA has compelled states to implement evidence-based practices (EBPs). Guidance to conduct independent technical review for EBPs is limited. The process for conducting reviews to two EBPs are illustrated. Rendering an evidence rating was difficult given conflicting findings across studies. The review process synthesizes a large body of research to inform child welfare practice. Abstract: The Family First Prevention Services Act (FFPSA) has compelled states to expand their priorities to implement evidence-based practices (EBPs) as a means to prevent foster care placement. While the states may opt to include EBPs already approved by the Administration for Children and Families (ACF), some state leaders are opting to commission an independent technical review for the EBP they would prefer to implement as part of their FFPSA plan. While the goal is for ACF to approve their plan and issue a temporary license, little guidance is provided on how to conduct technical reviews. Relying upon the expectations that ACF has outlined for each state, we illustrate the process for conducting reviews of SafeCare in Iowa and Utah and of Family-Centered Treatment in Arkansas. Despite FFPSA and ACF guidance, rendering an evidence rating was difficult given the variability in how some studies measured baseline equivalence, lack of robust testing methods, and conflicting findings across studies. We conclude with recommendations on addressing these challenges and strategies for conducting high-quality technical reviews. The review process offers an opportunity to synthesize a large body of research to inform child welfare practice.